Mine pit lakes : characteristics, predictive modeling, and sustainability - Castendyk, Devin N.; Eary, L. Edmond (Management technologies for metal mining influenced water ;, 2009)
Water quality of pit lakes is one of the most critical environmental issues facing the global mining industry. As ore grades decrease and operators strive to improve efficiency, the number of active pit mines will continue to outpace their underground counterparts in the years ahead. How will these water resources be protected for future generations while the mining industry continues to meet society's growing demands for raw materials? The key to solving this dilemma is accurately predicting the water quality in advance of open pit mining. This volume includes the latest thinking from dozens of internationally respected experts from Canada, Germany, Australia, and the United States. You'll learn both the theory and science of predicting pit lake water quality and get insights into the best practices of pit lake management.